A new LVI assisted PSFB DC-DC converter - Bakan, Ahmet Faruk (Tubitak Scientific & Technological Research Council Turkey, 2011)
In this study, a new Phase Shifted Full Bridge (PSFB) Pulse Width Modulated (PWM) isolated dc-dc converter is proposed. In the proposed converter, resonant inductor is replaced with Linear Variable Inductor (LVI) that is controlled by output current. The soft switching operation range is increased and the dependency of ZVS operation on the load current is decreased. The required energy for ZVS operation at low current levels is obtained by means of the high value of the LVI. The value of LVI decreases approximately linearly with increasing current. At high current levels parasitic resonance and duty cycle loss are decreased. By selecting the range of the LVI properly, the necessity of the dead time control between gate drive signals of the ICBM in the lagging leg is eliminated. A prototype of single phase IGBT-based inverter arc welding machine is implemented by using the proposed converter which operates at 75 kHz switching frequency and 5 kW output power. The experimental results taken from the converter show the feasibility of the proposed method.
Keywords: DC-DC converters; soft switching; ZVS; PSFB converter; linear variable inductor (LVI); FULL-BRIDGE CONVERTER; HIGH-POWER APPLICATIONS; ZERO-VOLTAGE; PWM CONVERTER; RANGE; Computer Science; Engineering